Blind-Sight vs. Degraded-Sight: Different Measures Tell a Different Story - Mazzi, Chiara; Bagattini, Chiara; Savazzi, Silvia (Frontiers in Psychology, 2016)
Blindsight patients can detect, localize and discriminate visual stimuli in their blind field, despite denying being able to see the stimuli. However, the literature documents cases of blindsight patients who demonstrated a preserved degree of awareness in their impaired visual field. The aim of this study is to investigate the nature of visual processing within the impaired visual field and to ask whether it reflects pure unconscious behavior or conscious, yet degrade, vision. A hemianopic patient (SL) with a complete lesion to the left primary visual cortex was tested. SL was asked to discriminate several stimulus features (orientation, color, contrast, motion) presented in her impaired visual field in a two-alternative forced-choice task. SL had to report her subjective experience: in the first experiment as "seen" or "guessed", whereas in the second experiment as the degree of clarity of her experience according to the Perception Awareness Scale (PAS). In the first experiment, SL demonstrated a performance above chance in the discrimination task for “guessed” trials, thus showing Type 1 blindsight. In the second experiment, however, SL showed above chance performance only when she reported a certain degree of awareness, thus showing that SL’s preserved discrimination ability relies on conscious vision. These data show that graded measures to assess awareness, which can better tap on the complexity of conscious experience, need to be used in order to differentiate genuine forms of blindsight from degraded conscious vision.